Expression of Formate-Tetrahydrofolate Ligase Did Not Improve Growth but Interferes With Nitrogen and Carbon Metabolism of Synechocystis sp. PCC 6803 - Song, Shanshan; Timm, Stefan; Lindner, Steffen N.; Reimann, Viktoria; Hess, Wolfgang R.; Hagemann, Martin; Brouwer, Eva-Maria (Frontiers in Microbiology, 2020)
The introduction of alternative CO2-fixing pathways in photoautotrophic organism may improve the efficiency of biological carbon fixation such as minimizing the carbon loss due to photorespiration. Here we analyzed the effects of creating a formate entry point into the primary metabolism of the cyanobacterium Synechocystis sp. PCC 6803. The formate-tetrahydrofolate ligase (FTL) from Methylobacterium extorquens AM1 was expressed in Synechocystis to enable formate assimilation and reducing the loss of fixed carbon in the photorespiratory pathway. Transgenic strains accumulated serine and 3-phosphoglycerate, and consumed more 2-phosphoglycolate and glycine, which seemed to reflect an efficient utilization of formate. However, labelling experiments showed that the serine accumulation was not due to the expected incorporation of formate. Subsequent DNA-microarray analysis revealed profound changes in transcript abundance due to ftl expression. Transcriptome changes were observed in relation to serine and glycine metabolism, C1-metabolism and particularly nitrogen assimilation. The data implied that ftl expression interfered with the signaling the carbon/nitrogen ratio in Synechocystis. Our results indicate that the expression of new enzymes could have a severe impact on the cellular regulatory network, which potentially hinders the establishment of newly designed pathways